Ultrasensitive iontronic pressure sensor based on microstructure ionogel dielectric layer for wearable electronics - Hairong Kou; Yuhang Pang; Libo Yang; Xiaoyong Zhang; Zhenzhen Shang; Lei Zhang; Liang Zhang; Yixin Shi; Zhiguo Gui; Youwen Ye; Shijie Song (Nanotechnology and Precision Engineering)
Flexible pressure sensors show great promise for applications in such fields as electronic skin, healthcare, and intelligent robotics. Traditional capacitive pressure sensors, however, face the problem of low sensitivity, which limits their wider application. In this paper, a flexible capacitive pressure sensor with microstructured ionization layer is fabricated by a sandwich-type process, with a low-cost and simple process of inverted molding with sandpapers being used to form a thermoplastic polyurethane elastomer ionic film with double-sided microstructure as the dielectric layer of the sensor, with silver nanowires as electrodes. The operating mechanism of this iontronic pressure sensor is analyzed using a graphical method, and the sensor is tested on a pressure platform. The test results show that the sensor has ultrahigh pressure sensitivities of 3.744 and 1.689 kPa−1 at low (0–20 kPa) and high (20–800 kPa) pressures, respectively, as well as a rapid response time (100 ms), and it exhibits good stability and repeatability. The sensor can be used for sensitive monitoring of activities such as finger bending, and for facial expression (smile, frown) recognition, as well as speech recognition.